One-year evaluation of the national health screening program for infants and children in Korea - Jin Soo Moon; Soon Young Lee; Baik-Lin Eun; Young Key Kim; Young Key Kim; Son Moon Shin; Hea Kyoung Lee; Hee Jung Chung (Korean Pediatric Society, 2010)
Purpose:Results of the Korea National Health Screening Program for Infants and Children, which was launched in November 2007, were evaluated for future research and policy development. Methods:Data from a total of 2,729,340 cases were analyzed. Five visiting ages, such as 4, 9, 18, 30, and 60 months, were included. Several parameters such as stunting, obesity, and positive rate of developmental screening were also analyzed. Telephone survey was performed in 1,035 users. For the provider survey, 262 doctors participated in our study. Results:The overall participation rate of users was 35.3%. This participation rate showed a decrement tendency to old age and low income. Only 6.9% of users participated in oral screening. Health screening was performed mainly in private clinics (82.6%). The recall rate of 4 months program users at the age of 9 months was 57.3%. The positive rate of screening was 3.1%, and was higher in the low-income group. By telephone survey, users reported that questionnaires were not difficult (94%) and overall satisfaction was good (73%). Longer duration of counseling was related with more satisfied users. Counseling and health education were helpful to users (73.2%). Doctors agreed that this program was helpful to children (98.5%). Conclusion:Korea National Health Screening Program for Infants and Children was launched successfully. Participation rate should be improved, and a quality control program needs to be developed. More intensive support following this program for children of low-income families may lead to effective interventions in controlling health inequality. Periodic update of guidelines is also needed.